Dampak Penggunaan Gadget dan Cara Penaggulanganya pada Peserta Didik Kelas V di SDN Ende 5 - Chatarina Novianti; Felix Welu; Yuliana Sepe Wangge; R.A Yunita Umar; Maria Irmagardis Pao; Margaretha Alaqok Tango Demu (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Gadgets are small electronic devices that have various specialized functions. In addition, a gadget can also be interpreted as a sophisticated device that contains various applications. These applications themselves are then used as a source of information, social networking, hobbies, creativity, and much more. Gadgets are used by parents, teenagers and early childhood who feel happy and even addicted to using them. So that for early childhood who is not given a companion or guidance can cause a negative impact on early childhood development. There are objectives, namely to find out what impact the use of gadgets has, to find out the signs of gadget addiction in children, to find out how to reduce the adverse effects of gadgets, to find out how to overcome gadget addiction, to find out the characteristics and effects of gadget addiction. This activity was conducted at SDN Ende 5 using a qualitative approach method. The results showed that gadgets are indeed very useful for life, but can cause negative things, including to elementary school children who make excessive social and emotional development. The adverse effects on children are closed personalities, sleep disorders, tantrums, violent behavior, fading creativity and the threat of cyberbullying. The solution is to limit the use of gadgets, supervise children when playing gadgets and give children the right time to play gadgets.